2219. Treatment Uptake for Hepatitis C Virus Infection in the Veterans Affairs Healthcare System in the Era of Directly Acting Antiviral Agents: An ERCHIVES Study. (26th November 2018) - Butt, Adeel Ajwad; Yan, Peng; Lo Re, Vincent; Shaikh, Obaid; ,
Abstract: Background: Knowledge about HCV treatment uptake, regimens and providers in the era of all-oral directly acting antiviral agents is critical for patients, providers, payers and policy makers. Our objective was to determine the number of persons initiated on HCV treatment over time, and trends in providers who initiate treatment Methods: Among all HCV+ persons in ERCHIVES from 2001 to 2017, we identified all persons who initiated HCV treatment and medical specialty of the provider initiating treatment. Results were tabulated by VA fiscal year. Results: A total of 108, 133 persons were initiated on treatment (Figure 1). Sofosbuvir-based regimens were the most commonly used regimens, accounting for nearly two-thirds of all DAA regimens. Gastroenterologists/hepatologist were the most common initiators of treatment in the pre-DAA era accounting for 26.7% of all prescriptions in 2001–2011 but only 10.3% in 2017 (Figure 2). Allied health professionals accounted for only 7.2% of treatment initiations in the 2001–2011 period but were the most frequent prescribers in 2017 (22.2%). Ratio of persons initiated on treatment to new HCV diagnoses reversed in 2013 for HCV monoinfected persons and in 2014 for HCV/HIV coinfected persons, with new treatment initiations far outnumbering new infections. Conclusion: There has been a dramatic increase in HCV treatment uptake in the VA healthcare system with the approval of newer all-oral DAA regimens. Treatment paradigm appears to be shifting toward lesser gastroenterologists/hepatologists and more allied health professionals treating HCV. Disclosures: A. Ajwad Butt, Gilead: Grant Investigator, Research grant.